1997
DOI: 10.1002/(sici)1096-9063(199705)50:1<21::aid-ps550>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Endosulfan in Cotton Soil under Sub-tropical Conditions of Northern India

Abstract: Terrestrial field studies were conducted with endosulfan during the 1989–90 Kharif season in bare cotton soil, to investigate the fate of endosulfan and its downward movement under sub‐tropical conditions of northern India. Field experiments consisted of spray application of endosulfan at 875 g ha‐1 42 and 63 days after the assumed date of sowing in two separate treatments. Soil samples drawn periodically from different depths were analysed by GC‐ECD (Ni63) for endosulfan and its breakdown products. Dissipatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 4 publications
5
27
0
5
Order By: Relevance
“…The beta isomer persisted longer than alpha isomer. These results confirm the observations of Kathpal, Singh, Dhankar, and Singh (1997). Though alpha isomer makes up 70% of active ingredient in commercial formulations, it could be detected in soils only immediately after spray because of its high volatility.…”
Section: Distribution Of Endosulfan Residues In Soilsupporting
confidence: 89%
“…The beta isomer persisted longer than alpha isomer. These results confirm the observations of Kathpal, Singh, Dhankar, and Singh (1997). Though alpha isomer makes up 70% of active ingredient in commercial formulations, it could be detected in soils only immediately after spray because of its high volatility.…”
Section: Distribution Of Endosulfan Residues In Soilsupporting
confidence: 89%
“…In the environment, the cyclic sulfite group of endosulfan can be oxidized to the corresponding sulfate (endosulfan sulfate) (Chandler et al 1991; Guerin et al 1992; Kathpal et al 1997), which is persistent than its parents (Guerin 2001). In China, endosulfan is currently used as pesticide for cotton, wheat, tea, tobacco, and apple tree (Jia et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…[4] Moreover, volatilization is the dominant form in dissipation of endosulfan and its metabolites from the environment. [5] In another study, it was reported that the rate of degradation of endosulfan in soil increased significantly with increasing soil alkalinity, at pH 3 almost no degradation of endosulfan took place, slight degradation at pH 5, significant increase at pH 7.5-8.5, and at pH 10-12 almost all the added endosulfan was rapidly converted to endosulfan diol. The same study reported that soil moisture and aeration affected the degradation rate of endosulfan and the pathways of its metabolism, as its degradation rates decreased significantly in flooded soils compared to nonflooded soils.…”
Section: Introductionmentioning
confidence: 97%